2005
DOI: 10.1007/s00464-004-2172-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and open gastric resections for malignant lesions: A prospective comparative study

Abstract: The totally laparoscopic approach to total and partial gastrectomies had good results and was proven to be a feasible and safe procedure. In addition, the laparoscopic procedures are superior to open surgeries in terms of faster postoperative recovery, shorter hospital stay, and better cosmetic outcomes. A totally laparoscopic approach for early and advanced gastric cancer can obtain adequate margins and follow oncologic principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 24 publications
9
117
3
Order By: Relevance
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…In retrospective reports about LADG, the proportions of patients who developed anastomotic leakage were quite different (1.7%-14%) [8,9,12], while that of patients who developed pancreatic fi stula formation was 1.0% [9]. The primary endpoint in the present prospective study demonstrated that the proportion of patients who developed these two postoperative complications was lower than expected, compared with the proportions in these retrospective reports.…”
Section: Discussionmentioning
confidence: 48%
“…Although whether this modality is appropriate for cancer treatment remains a concern, the technical diffi culties of LADG have been gradually solved. Several studies have reported that LADG allows a better quality-of-life outcome than an open distal gastrectomy (ODG) [6][7][8][9][10][11]. Although several studies have reported that LADG is a safe procedure with regard to morbidity and mortality [12,13], other studies have reported that LADG has a higher risk of surgical morbidities such as anastomotic leakage, stenosis, and pancreatic fi stula formation than ODG [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…After reading the full texts of the remaining papers, 24 studies were removed as they only reported the outcomes of LG for AGC whereas no controlled or matched cases treated by OG were available. Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63].…”
Section: Resultsmentioning
confidence: 99%